PENYEBAB KETERLAMBATAN PELAYANAN PENUMPANG WHEELCHAIR MASKAPAI SAUDI ARABIAN AIRLINES RUTE JEDDAH-JAKARTA - Zaini, Muhammad; NOVIANTI, NOVIANTI (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2015)
Delay is supposedly not to be a usual thing. The researchers, using the field research and literature method and fishbone analysis, found five factors: first, the obstacles in processing wheelchair for passenger arrivals with percentage at 86.8%; second, no wheelchair for passenger from the employees with a percentage of 81.6%; third, insufficient time to process the services with a percentage of 78.9%; fourth, the inadequate number of wheelchair with a percentage of 60.5%; the last, wheelchair passengers had to wait to use the lift with a percentage of 63.16%. To overcome these, the management should add the employees number and the overtime hours, re-set the absent matches with airline flight schedule, provide employees training, increase the number of wheelchair, repair the broken wheelchair, and convey complaints from passengers using wheelchair to Angkasa Pura II to increase the number of existing lifts.